Financial characteristics, human development index, and performance: a study of local governments in Indonesia - Dany Adi Saputra; Lina Nur Ardila; Purnama Siddi; Bambang Sutopo (Jurnal Akuntansi dan Auditing Indonesia, 2018)
This study aims to examine whether the financial characteristics and human development index (HDI) are associated with the performance of local governments administration in Indonesia. The sample consists of 385 local governments classifying expenditures into operating and capital expenditures (Sample 1) and 53 local governments classified expenditures into direct and indirect expenditures (Sample 2). Regression result for Sample 1 indicate that special allocation funds (dana alokasi khusus, DAK) have a positive relationship with performance while general allocation funds (dana alokasi umum, DAU) and land expenditure are negatively related to performance. For Sample 2, revenue risk and DAU are negatively related to performance, whereas revenue sharing funds (dana bagi hasil, DBH) have a positive relationship with performance. Audit opinion and human development index are positively related to performance either for Sample 1 or Sample 2. These findings suggest that financial characteristics and human development index can be used as a consideration in determining financial policy and evaluation of local governments.